Beyond Instrumentalization: Lived Religion, Politics, and Justice in Indonesian Muslim Environmentalisms - Bagir, Zainal Abidin (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2025)
Indonesian “green Islam” has been celebrated as a prominent case of religious engagement with environmental issues. This article reviews recent empirical and theoretical literature on religion and environment in Indonesia and beyond. It assesses some trends in the discourse and suggest new directions in the study of Muslim environmental engagement. I start with problematizing a question that stands out in the literature about the effectiveness of the so-called “green Islam:” does it contribute to the achievement of environmentalist goals? I suggest an expansion of the Islam and environment discourse in several directions. From the critical perspective of religious studies, I suggest paying closer attention to lived Islam, in contrast to insular theologizing that revolves around texts without attention to practices. I then argue for engaging with questions of justice and politics of environmentalism. Such an approach reveals that religions, including certain versions of Muslim understanding, are ecologically ambivalent.